ELECTROCHEMICAL BEHAVIOR OF SILVER IN A POTASSIUM FERROCYANIDE SOLUTION - A.B. Bayeshov,; E.Zh. Tuleshova,; A.K. Baeshova,; M.A. Ozler, (Academic Scientific Journal of Chemistry, 2020)
One of the main priorities of the innovative industrialization of the country is the development of metallurgy and the production of finished products. In this regard, the application of new methods for producing metals and their compounds or extracting them from solutions is an important task of our time. One of the promising methods applied currently is the polarization by alternating current of industrial frequency, which arouses the interest of researchers both from the point of view of oxidation and destruction of the passivating film. The peculiarity of the processes occurring under the action of industrial alternating current is that, by changing the direction of the current, it is possible to remove the oxide film and create conditions for the metal to further dissolve. The work shows the distinctive features of electrochemical processes occurring on a silver electrode during electrolysis by industrial alternating current in a solution of ferrosyne-sintered potassium by the method of rational mathematical planning. The optimal conditions for the dissolution of silver are determined by studying the effect of current density at the electrodes, the concentration and temperature of the electrolyte, the duration of the electrolysis and the frequency of the alternating current. It is shown that when polarized with an alternating current of silver in a pair with a titanium electrode, the passivation process of the silver electrode is eliminated and the dissolution rate of the metal increases